On the Size of Minimal Unsatisfiable Formulas - Lee, Choongbum (The Electronic Journal of Combinatorics, 2009)
An unsatisfiable formula is called minimal if it becomes satisfiable whenever any of its clauses are removed. We construct minimal unsatisfiable k-SAT formulas with Ω(n^k) clauses for k ≥ 3, thereby negatively answering a question of Rosenfeld. This should be compared to the result of Lovász [Studia Scientiarum Mathematicarum Hungarica 11, 1974, p113-114] which asserts that a critically 3-chromatic k-uniform hypergraph can have at most nk-1 edges.